2011
DOI: 10.1021/jf1042486
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Acrylamide Mitigation Strategies on Industrial Production of French Fries: Challenges and Pitfalls

Abstract: This study evaluated various additives or process aids on the industrial production of French fries, based on their acrylamide mitigation potential and other quality parameters. The application of acetic and citric acid, calcium lactate and asparaginase was investigated on the production of frozen par-fried French fries at the beginning and end of the 2008 and 2009 potato storage season. Despite the fact that some of these treatments significantly reduced acrylamide content of the final product in preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
0
13
0
4
Order By: Relevance
“…The levels of reducing sugars and free asparagine in raw potatoes are greatly influenced by the genotype of the potato. 22,51 Additionally, the content of sugars in potatoes is also affected by the storage temperature, being most prominent at the conventional storage temperature (4 • C).…”
Section: Influence Of Aa Precursorsmentioning
confidence: 99%
“…The levels of reducing sugars and free asparagine in raw potatoes are greatly influenced by the genotype of the potato. 22,51 Additionally, the content of sugars in potatoes is also affected by the storage temperature, being most prominent at the conventional storage temperature (4 • C).…”
Section: Influence Of Aa Precursorsmentioning
confidence: 99%
“…These studies found that the amount of acrylamide was extremely higher in fried potato products (such as French fries and potato chips) followed by cereals, crisp breads, biscuits and other bakery products. Concentration and dietary intake of food have significant variations, which depends upon cooking methods [21,[34][35][36][37][38][39][40][41][42]. Factors such as difference in food composition, high temperature (more than 120°C), and high carbohydrate, free asparagine, reducing sugars, pH, water content, ammonium bicarbonate and high concentration of competing amino acids could be the sources for variation in acrylamide level [43][44][45][46][47].…”
Section: Occurrence and Dietary Intakementioning
confidence: 99%
“…The reduction of asparagine is one of these ways and can be achieved from the use of the enzyme asparaginase [10][11][12][13]. The available commercial enzymes have been tested in chips [14], with promising results showing 90% reduction of acrylamide formation in the final product and no changes in the sensory characteristics [15].…”
Section: Introductionmentioning
confidence: 99%